Sharia Compliance and Economic Resilience of Women-Led SMEs in Madura Indonesia - Galuh Widitya Qomaro; Nasrulloh Nasrulloh; Nurdeng Deuraseh (Journal of Islamic Civilization, 2024)
This study examines the impact of Sharia compliance on the economic resilience of women-led micro and small enterprises (MSEs) in Madura, Indonesia. Sharia principles, which emphasize the prohibition of riba (interest), gharar (ambiguity), maysir (gambling), and unethical activities, along with fairness and risk-sharing, align closely with the cultural and religious values of Madura. Using a mixed-methods approach, quantitative data were gathered through surveys from 100 women entrepreneurs, and qualitative insights were obtained through in-depth interviews with 20 selected participants. The results indicate that adherence to Sharia compliance positively and significantly enhances financial stability, facilitates ethical investment diversification, and fosters community trust. This alignment with Islamic principles not only strengthens the economic resilience of businesses but also contributes to broader social well-being. The findings suggest that Sharia compliance serves as a strategic foundation for sustainable development in culturally rooted economies like Madura. Future research is encouraged to explore this model in other sectors and regions to expand its applicability.